Two communities, one highway and the fight for clean air: the role of political history in shaping community engagement and environmental health research translation. - Sprague Martinez, Linda.; Dimitri, Noelle.; Ron, Sharon.; Hudda, Neelakshi.; Zamore, Wig.; Lowe, Lydia.; Echevarria, Ben.; Durant, John L.; Brugge, Doug.; Reisner, Ellin. (Tufts University. Tisch Library., 2020)
Keywords: Traffic related air pollution (TRAP); research and action, Community based participatory research, Public health action.; Springer Open.